ANALISIS FRAMING PEMBERITAAN MENGENAI ARAB SAUDI PADA MEDIA ONLINE DETIKCOM - Muhammad Fikri Ardiansyah (Program Studi Komunikasi dan Penyiaran Islam, 2022)
This study examines the problem formulated as follows: “There is negative news about Saudi Arabia in Indonesia. One example is the news about the opening of a Dog Cafe in Saudi Arabia under the name